The German REFINA R+D program for the reduction of greenfield development and for promoting sustainable land management - hauschild, maike; wittmann, uwe; enders, reiner (Italian journal of engineering geology and environment, 2007)
The REFINA R+D program for the reduction of Greenfield development and for promoting sustainable land management is a new German research programme funded by the BMBF, the German Federal Ministry of Education and Research. The German federal government has set a goal of reducing land consumption to 30 hectares (75 acres) per day in 2020 as part of the German National Strategy for Sustainable Development (NSSD). In order to provide a scientifically reliable basis for decisions and measures, BMBF launched the R+D Program REFINA in October 2004. REFINA will grant the development and testing of innovative concepts for the reduction of greenfield development to achieve a multitude of goals such as e.g. protection of the environment and nature, economical growth, socially balanced housing, architectural urban quality, and mobility. The R+D effort includes ecological, economical, and social aspects like equality, participation and education. REFINA has a funding grant volume of 20 million Euros and lasts for five years.First projects started in December 2005.